INCONTINENCE-ASSOCIATED DERMATITIS: PREVALENCE AND ASSOCIATED FACTORS IN INTENSIVE CARE UNIT (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To analyze the point prevalence of incontinence-associated dermatitis (IAD) and associated factors in adult patients admitted to Intensive Care Units (ICUs). Method: A cross-sectional, observational, retrospective study carried out with 105 patients in the ICU of three university hospitals located in the state of São Paulo. The demographic and clinical variables and IAD come from the database of the research project “Prevalence of pressure injuries in the Intensive Care Unit,” composed of information from medical records and physical examination. Data were analyzed using descriptive and inferential statistics. The study was approved by the Research Ethics Committee of the proposing institution. Results: Of the 105 patients, 58 (55.24%) were male, with a mean age of 55.76 years (SD = 16.39), 105 (91.3%) had a urinary catheter and 89.4% wore diapers. Ten patients had IAD, with a point prevalence of 9.52%. The factor associated with IAD was admission due to trauma (p = 0.02). Conclusion: Studies on IAD are essential for quality, well-structured and grounded nursing care, especially in the care of critically ill patients.